Elastomeric Polymers For Blast And Ballistic Retrofitting Of Structures - Somarathna, H.M.C.C.; Raman, S.N.; Mutalib, A.A.; Badri, K.H. (My University, 2015)
In many parts of the world, terrorism has become a major threat to nations, and terrorist activities and accidental explosions have been directed towards the destruction of buildings and critical infrastructures. As a result, almost every new development requires the consideration of safety and security aspects such that even a new building incorporates protective engineering features in its design. In this aspect, researchers have been investigating the use of elastomeric polymers (such as polyurethane and polyurea) for structural retrofitting applications due to attractive characteristics and morphology exhibited by these materials. This paper provides a review on this novel approach of strengthening structural elements and systems to enhance their capacity against blast and ballistic threats. The discussions in this review have been focussed on the application of this technique on the most widely used structural systems of masonry, concrete, metallic and composite structural systems. This technique offers an alternative to existing strengthening techniques in protecting structures against the risks of blast, ballistic and impact loads.
Keywords: Blast loading; ballistic loading